Illegal Logging and Its Impact on Forest Ecosystems in Southeast Asia - Aziz, Safiullah; Akhtar, Shazia; Amin, Rafiullah (Yayasan Adra Karima Hubbi, 2024)
Illegal logging poses a significant threat to forest ecosystems in Southeast Asia, compromising biodiversity, disrupting ecological balance, and undermining sustainable development efforts. The region's rich biodiversity and vital ecosystem services are increasingly jeopardized by unregulated logging practices, necessitating a thorough investigation of its impacts. This research aims to assess the extent of illegal logging in Southeast Asia and its effects on forest ecosystems. The study seeks to identify key drivers of illegal logging and analyze its implications for biodiversity and local communities. A mixed-methods approach was employed, combining quantitative data from satellite imagery and forest cover assessments with qualitative interviews of stakeholders, including local communities, government officials, and NGO representatives. Case studies from Indonesia, Malaysia, and Thailand were analyzed to provide insights into the dynamics of illegal logging. Findings reveal that illegal logging significantly contributes to deforestation and habitat loss, leading to declines in species populations and disruptions in ecosystem functions. Local communities reported negative impacts on their livelihoods and increased conflicts with wildlife as a result of habitat degradation. The study concludes that addressing illegal logging is crucial for the conservation of forest ecosystems in Southeast Asia. Effective governance, community engagement, and sustainable forest management practices are essential to combat illegal activities and protect biodiversity. Collaborative efforts among stakeholders will be vital for creating resilient forest ecosystems in the region.